SPS measures and possible market access implications for agricultural trade in the Doha Round: An analysis of systemic issues - Murali Kallummal (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2012)
Even as the Doha Round seeks to address tariff liberalization issues in a comprehensive manner, the imbalance in the outcome of market access for developing country exporters will be particularly glaring in the case of fresh agricultural and processed food products. There is growing evidence that protectionism from the usage of non-tariff barriers such as SPS measures has increased tremendously in the recent past. This paper discusses an analysis of the SPS notifications made by WTO Member countries from 1995 to July 2010, which found that 53 per cent of total SPS notifications during that period were made by developing countries. However, developed countries are using their national standards to a more significant extent than Doha developing countries. The adoption of differing national standards creates significant barriers to trade, with developed country standards being higher in many cases. Frequently, these standards are not matched by the developing countries' technological capabilities. Furthermore, there are some systemic issues in the SPS Agreement and its implementation that bias its outcome against developing and least developed countries. Thus, there is an urgent need for discipline in the usage of SPS measures as a tool for disguised protectionism. This can be best achieved by harmonizing the standards across WTO Members under the three intra-governmental bodies already identified by the SPS Agreement. Given the principle of national treatment, this means that the imperative for developing country governments to support the technological upgrading of their domestic agricultural sectors has become extremely urgent.
Keywords: F13; F14; O19; 330; Agreement on Sanitary and Phytosanitary Measures; transparency; non-tariff measures; ad-valorem equivalents; technological gap; harmonization; WTO